Mesocarnivore on the move: an updated review on the spread and ecological effects of invasive Nyctereutes procyonoides - Katherine Majewski; Vanessa Nadine Gris; Takako Miyabe-Nishiwaki; Andrew J. J. MacIntosh (Biological Invasions, 2026)

Implications of gear selection for monitoring benthic fish communities in the Beaufort Sea - Duane E. Stevenson; Stan Kotwicki; Brenda Norcross; Andrew Majewski (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Offshore demersal fish community structure and habitat associations in Amundsen Gulf, Canadian Arctic - Andrew R. Majewski; Krystal Woodard; Andrea Niemi; Sheila Atchison; Jane Eert; Shannon MacPhee; James D. Reist (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Phycotoxins in bivalves from the western Canadian Arctic: The first evidence of toxigenicity - Monika Pućko; Wade Rourke; Rachel Hussherr; Philippe Archambault; Jane Eert; Andrew R. Majewski; Andrea Niemi; Jim Reist; Christine Michel (Harmful Algae, 2023)

New species of Gromia (Protista, Rhizaria) from South Georgia and the Falkland Islands - Andrew J. Gooday; Maria Holzmann; Wojciech Majewski; Jan Pawlowski (Polar Biology, 2022)

Cod movement ecology in a warming world: Circumpolar arctic gadids - Harri Pettitt‐Wade; Lisa L. Loseto; Andrew Majewski; Nigel E. Hussey (Fish and Fisheries, 2021)
Understanding fish movement in the Arctic is paramount during the current era of rapidly warming seas, receding sea ice and associated shifting species distributions and fishing effort. We synthesized the literature and identified key knowledge gaps on the movement ecology of Arctic cod ( Boreogadus saida ) and Polar/Ice cod ( Arctogadus glacialis , both Gadidae) in the context of climate change. Standardized web‐based English‐language literature searches yielded 51 articles directly relevant and 122 indirectly relevant for the movement ecology of these species combined. Most articles were primarily relevant to B. saida (85% of total filtered articles), occurred during open water season (49/38%) with focus on distribution (32/22%), predators (30/22%), seasonal spawning/feeding movements (22/19%), sea ice association (22/26%), climate change (20/15%) and vertical movements (17/19%) with few focused on horizontal dynamics (3/0%; B . saida / A . glacialis , respectively). Disproportionate data resolution has resulted in greater predictive power of movement models for the European (29% of articles) and North American (86%) Arctic regions relative to the logistically challenging Central Arctic Ocean and Russian‐Siberian Arctic shelves (both 7%). The movements of circumpolar Arctic gadids are dependent on complex dynamics that include regional currents, the longevity of ice‐flows and polynyas, water stratification and coastal hydrology. Dependence on these interactive and often co‐dependent processes highlights major pathways and barriers to movement and distribution at higher latitudes. Despite a recent increase in impactful research, there is a critical need for more direct research on circumpolar gadid movements to aid understanding of climate change impacts on Arctic ecosystems and fisheries.

Mitochondrial genome diversity and population mitogenomics of polar cod (Boreogadus saida) and Arctic dwelling gadoids - Robert E. Wilson; Sarah A. Sonsthagen; Noel Smé; A. J. Gharrett; Andrew R. Majewski; Kate Wedemeyer; R. John Nelson; Sandra L. Talbot (Polar Biology, 2020)

Pelagic production and the recruitment of juvenile polar cod Boreogadus saida in Canadian Arctic seas - Mathieu LeBlanc; Maxime Geoffroy; Caroline Bouchard; Stéphane Gauthier; Andrew Majewski; James D. Reist; Louis Fortier (Polar Biology, 2020)
Previous work found that an earlier ice breakup favors the recruitment of juvenile polar cod ( Boreogadus saida ) by enabling early hatchers to survive and reach a large size by late summer thanks to a long growth season. We tested the hypothesis that, in addition to a long growth season, an earlier ice breakup provides superior feeding conditions for young polar cod by enhancing microalgal and zooplankton production over the summer months. Ice cover and surface chlorophyll a were derived from satellite observations, and zooplankton and juvenile cod biomass were estimated by hydroacoustics in ten regions of the Canadian Arctic over a period of 11 years. Earlier breakups resulted in earlier phytoplankton blooms. Zooplankton backscatter in August increased with earlier breakup and bloom, and plateaued at chlorophyll a > 1 mg m −3 . Juvenile cod biomass in August increased with an earlier breakup, and plateaued at a zooplankton backscatter > 5 m 2 nmi −2 , supporting the hypothesis that higher food availability promotes the growth and survival of age-0 fish in years of early ice melt. However, there was little evidence that late summer biomass of either zooplankton or age-0 polar cod benefitted from ice breakup occurring prior to June. On average, zooplankton standing stock was similar in the Southern Beaufort Sea and the North Water-Lancaster Sound polynya complex, but juvenile cod biomass was higher in the Beaufort Sea. Intense avian predation could explain the lower biomass of juvenile cod in the polynya complex, confirming its reputation as a biological hotspot for energy transfer to higher trophic levels.

Trophic variability of Arctic fishes in the Canadian Beaufort Sea: a fatty acids and stable isotopes approach - Carolina Giraldo; Ashley Stasko; Emily S. Choy; Bruno Rosenberg; Andrew Majewski; Michael Power; Heidi Swanson; Lisa Loseto; James D. Reist (Polar Biology, 2016)

Distribution and diet of demersal Arctic Cod, Boreogadus saida, in relation to habitat characteristics in the Canadian Beaufort Sea - Andrew R. Majewski; Wojciech Walkusz; Brittany R. Lynn; Sheila Atchison; Jane Eert; James D. Reist (Polar Biology, 2016)

Vertical segregation of age-0 and age-1+ polar cod (Boreogadus saida) over the annual cycle in the Canadian Beaufort Sea - Maxime Geoffroy; Andrew Majewski; Mathieu LeBlanc; Stéphane Gauthier; Wojciech Walkusz; James D. Reist; Louis Fortier (Polar Biology, 2016)

A novel rearrangement of occludin causes brain calcification and renal dysfunction - Marissa A. LeBlanc; Lynette S. Penney; Daniel Gaston; Yuhao Shi; Erika Aberg; Mathew Nightingale; Haiyan Jiang; Roxanne M. Gillett; Somayyeh Fahiminiya; Christine Macgillivray; Ellen P. Wood; Philip D. Acott; et al. (Human Genetics, 2013)

Genetic differentiation between Arctic and Antarctic monothalamous foraminiferans - Jan Pawlowski; Wojciech Majewski; David Longet; Jackie Guiard; Tomas Cedhagen; Andrew J. Gooday; Sergey Korsun; Andrea A. Habura; Samuel S. Bowser (Polar Biology, 2008)